Knowledge of heart disease risk factors among non-academic staff at School Of Health Sciences Universiti Sains Malaysia - Alang, Nur Hamimi Che (Universiti Sains Malaysia, 2016)
Cardiovascular disease is a disease that is reaching to epidemic proportion worldwide problem that involves both developed and developing countries. In Malaysia, death happens due to cardiovascular disease was 20-25%. The aim of this descriptive and crosssectional study was to determine the knowledge of the heart disease (HD) risk factors among non-academic staff at School of Health Sciences, Universiti Sains Malaysia. Ninety five respondents in this study were recruited by using simple random sampling technique, from January until February 2016. A self-administered heart disease fact questionnaire (HDFQ) was used to collect the data. Data was analyzed using the Statistical Package for the Social Sciences (SPSS) version 22.0. The result showed that non-academic staff at School of Health Sciences had moderate level of knowledge of HD risk factors 15.69 (4.840). The study also found that there was no significant association between age and the level of knowledge on FID risk factors (p= 0.123). Furthermore, there was a significant association between educational status with the level of knowledge of FID risk factors (p= 0.004). There was a significant association between family history and the level of knowledge of FID risk factors (p=0.006). Knowledge on heart diseases risk factors was influenced by educational levels and family history of cardiovascular diseases among respondents. Findings indicated a need for health promotion on knowledge of heart diseases risk factors and screening program to improve public understanding about heart disease. Hence, the primary prevention is important to increase the level of knowledge in helping individuals to make better decisions regarding their health care.